Motivational Differences in Women’s Perceptions, Compensation Strategies, and Intentions to Eat in Response to Body-Related Self-Discrepancies - Barbeau-Julien, Kheana (Université d'Ottawa / University of Ottawa, 2023)
This thesis examined how women cope with various types of body-related discrepancies, such as those related to their physical appearance, and their effects on eating behavior. The Hierarchical Action-Based Model of Inconsistency Compensation, an integrative model comprising tenets from the action-based model of dissonance (Harmon-Jones et al., 2009) and Self-Determination Theory (Ryan & Deci, 2017), was used as a guiding framework to understand motivational differences in compensation processes and eating behavior following a body-related discrepancy. This objective was achieved through three studies broken down into two articles. The first study (Article 1; N = 398) used a mixed method cross-sectional design and examined the types of body-related discrepancies women face, their contextual elicitors, and motivational differences in the propensity of experiencing them. Following the recollection of such experiences, the associations between women’s motivation for eating regulation and eating intentions, and the mediating role of dissonance-based processes in these relationships, were examined. Results revealed that women, in general, experience discrepancies related to the appearance and care toward their body. These experiences were often elicited by body exposure (e.g., reflection in the mirror) and occurred in a non-social-evaluative context. Additionally, women with more controlled eating regulation experienced more discrepancies in eating quality and physical activity. Furthermore, results demonstrated that women with more autonomous eating regulation intended to engage in more healthy eating in response to a body-related discrepancy, whereas women with more controlled eating regulation intended to engage in more disordered eating. These distinct pathways were partly explained by differences in self-compassion, and consequently dissonance arousal, and selection of behavioral (versus cognitive) compensation strategies. The second study (Article 2; N = 107) replicated findings from Study 1 by exposing women to a mirror while being instructed to talk about their body in a non-social-evaluative (n = 52) or a social-evaluative (i.e., presence of two female judges; n = 55) context. Dissonance was experimentally manipulated in an additive fashion (i.e., mirror versus mirror and social evaluation) to determine whether motivational differences in dissonance processes and eating behaviors were contingent upon the evaluative nature of the context. Results partly replicated findings in Study 1, such that women with more autonomous eating regulation intended to engage in more healthy eating following mirror exposure (ME), and this relationship was partly explained by engagement in behavior modification strategies, whereas women with more controlled eating regulation intended to engage in more disordered eating following ME. These relationships persisted across ME conditions. Finally, the third study (Article 2; N = 199) used the same paradigm as Study 2 with the additional manipulation of women’s self-related body talk during ME, such that women were instructed to engage in positive/compassionate (social-evaluative n = 47; non-social-evaluative n = 52) or negative (social-evaluative n = 48; non-social-evaluative n = 52) body talk. This allowed us to observe the effects of positive and negative body talk on women’s eating behaviors and the moderating role of motivation following ME. Results demonstrated that women with more controlled eating regulation benefitted from counter-attitudinal (positive/compassionate) body talk during ME as indicated by more intent to engage in healthy eating behavior. Taken together, results suggest that increased salience of body-related discrepancies negatively affects women’s ability to regulate their eating if they do so for more controlled reasons. This is partly attributed to low emotion regulation resources and use of avoidant compensation strategies. However, these negative implications on their eating behavior can be alleviated via dissonance by facilitating the restructuring of body-related cognitions in contexts that typically elicit body-related discrepancies.
Keywords: motivation for eating regulation; body-related discrepancies; eating behavior; dissonance compensation; self-compassion